2013
DOI: 10.1371/journal.pntd.0002113
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Trypanosoma cruzi Infection among People Aged 15 to 89 Years Inhabiting the Department of Casanare (Colombia)

Abstract: The purpose of this study was to calculate the seroprevalence of Trypanosoma cruzi infection in a sample of inhabitants from a region considered to be at high risk of natural transmission of Chagas disease in Colombia. A cross-sectional study was conducted in subjects from 5 municipalities, recruited in urban and rural locations, distributed by gender according to the demographic information available. Socio-demographic information, history of potential exposure to insect vectors, blood donating, as well as sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
1
9
0
3
Order By: Relevance
“…The region has also high levels of seroprevalence in humans (16.91%), reported by Gutierrrez et al, 2013, supporting the hypothesis of high contact rates between insects and people (Gutierrez et al, 2013).…”
Section: Introductionsupporting
confidence: 60%
“…The region has also high levels of seroprevalence in humans (16.91%), reported by Gutierrrez et al, 2013, supporting the hypothesis of high contact rates between insects and people (Gutierrez et al, 2013).…”
Section: Introductionsupporting
confidence: 60%
“…Housing material is a known and important risk factor for Chagas disease . Our observation that this association is still present indicates that this aspect must be improved further in rural areas.…”
Section: Discussionmentioning
confidence: 79%
“…Housing material is a known and important risk factor for Chagas disease. 19,27 Our observation that this association is still present indicates that this aspect must be improved further in rural areas. However, we did not find the flooring material of the house to be a significant risk factor, in contrast to previous studies that found such an association.…”
Section: Discussionmentioning
confidence: 84%
“…The minimum sample size ( n ), needed to ensure the genes identified by Tiling Assembly and Cufflinks coincided with FL-cDNAs, was calculated using the following equation: , where 100 ; 22 N represents the total number of discrepant genes; E is the margin of error, which was set to 5%; the critical value was set to 1.96 based on a 95% confidence level ( c ); and r was set to 60% since this value was the expected discrepancy rate contributed to alternative splicing.…”
Section: Methodsmentioning
confidence: 99%